SHOPPERS’ LOYALTY IN PASAR DUKUH MENANGGAL - Anastasia Audrey Oenaryo; Liza Agustina Maureen Nelloh (Jurnal Manajemen dan Wirausaha, 2013)
This study improved the antecedents of loyalty such as price sensitivity, shopping values (utilitarian values and hedonic values) and satisfaction in Pasar Dukuh Menanggal Surabaya. It consists of 145 respondents and the result tested by SEM. The result showed that price sensitivity has insignificant toward hedonic value. Shopping values are positively influencing satisfaction but utilitarian value plays a big role on this path. Moreover, the management should improve the necessity of customers to achieve shopping values, satisfaction and loyalty.